Studies on structural and biochemical mechanism of resistance in groundnut to Puccinia arachidis - SRIKANT KULKARNI, GURURAJ SUNKAD* and (Indian Phytopathology, 2006)
Mechanism of resistance on the basis of structural and biochemical changes in resistant (GPBD4 and DH- 2), moderately resistant (K-134 and R-8808) and susceptible (KRG-1 and TMV-2) genotypes of groundnut were studied. Resistant and moderately resistant genotypes were characterized by higher cuticular and epidermal cell thickness with lesser epidermal cells, size (length, breadth) and number of stomata and more wax content at later stages of crop growth. Resistant and moderately resistant genotypes recorded more sugars, phenol, ortho-dihydroxy phenol and protein contents than susceptible ones.